2021
DOI: 10.1590/s0004-2803.202100000-19
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and colorectal neoplasms: a concise review

Abstract: Helicobacter pylori is the main etiological agent of all malignant tumors caused by an infectious disease. It is a major, at times dominant, factor in the pathogenesis of a large spectrum of diseases such as acute and chronic gastritis, gastric and duodenal ulcers, gastric carcinoma, and lymphoma. Epidemiological and experimental studies suggest that H. pylori chronic infection may be related to different extragastric diseases, including colorectal neoplasms. This concise review aims to explore the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Besides its clear involvement in gastric carcinogenesis, recent studies have reported an association between Helicobacter pylori and CRC [42,43]. A study involving 812,736 individuals found that Helicobacter pylori infection is associated with an 18% higher risk of developing CRC and a 12% higher risk of death from CRC [44].…”
Section: Gut Microbiota and Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides its clear involvement in gastric carcinogenesis, recent studies have reported an association between Helicobacter pylori and CRC [42,43]. A study involving 812,736 individuals found that Helicobacter pylori infection is associated with an 18% higher risk of developing CRC and a 12% higher risk of death from CRC [44].…”
Section: Gut Microbiota and Crcmentioning
confidence: 99%
“…A study involving 812,736 individuals found that Helicobacter pylori infection is associated with an 18% higher risk of developing CRC and a 12% higher risk of death from CRC [44]. An explanation for this pathogenic relationship can be found in the disruption of cell proliferation caused by the vacA toxin, which is produced by Helicobacter pylori [43]. Ralser et al identified a specific immune pattern associated with Helicobacter pylori infection, characterized by a reduction in regulatory T cells and proinflammatory T cells [45].…”
Section: Gut Microbiota and Crcmentioning
confidence: 99%
“… 98 Therefore, H pylori eradication might have an impact on the prevention of colorectal neoplasm formation. 99 , 100 …”
Section: Relationship Between Helicobacter Pylori ...mentioning
confidence: 99%
“…98 Therefore, H pylori eradication might have an impact on the prevention of colorectal neoplasm formation. 99,100 Based on our review, the diversity of the gut microbiota associated inflammatory responses, immune regulation, and metabolic changes have played an important role in the development and progression of colorectal adenomas (Figure 1).…”
Section: Relationship Between Intestinal Metabolites and Colorectal A...mentioning
confidence: 99%
“…In addition to gastric cancer, the association between H. pylori infection and CRC has also been reported ( 14 ), but the mechanism remains elusive. One possibility is that the vacA toxin produced by H. pylori results in cell proliferation dysregulation, and thus, induces CRC initiation and progression ( 15 ). Similarly, B. fragilis toxin (BFT) activates Wnt and NF-κB signaling, leading to DNA damage and the initiation and promotion of CRC ( 16 ).…”
Section: Microbiota: Friend and Foementioning
confidence: 99%